Treatment and functional outcomes of complex tibial fractures in children and adolescents using the Ilizarov method. (March 2018) - Messner, J.; Johnson, L.; Taylor, D. M.; Harwood, P.; Britten, S.; Foster, P.
Abstract : Aims: The aim of this study was to report the clinical, functional and radiological outcomes of children and adolescents with tibial fractures treated using the Ilizarov method. Patients and Methods: Between 2013 and 2016 a total of 74 children with 75 tibial fractures underwent treatment at our major trauma centre using an Ilizarov frame. Demographic and clinical information from a prospective database was supplemented by routine functional and psychological assessment and a retrospective review of the notes and radiographs. Results : Of the 75 fractures, 26 (35%) were open injuries, of which six (8%) had segmental bone loss. There were associated physeal injuries in 18 (24%), and 12 (16%) involved conversion of treatment following failure of previous management. The remaining children had a closed unstable fracture or significant soft-tissue compromise. The median follow-up was 16 months (7 to 31). All fractures united with a median duration in a frame of 3.6 months (interquartile range 3.1 to 4.6); there was no significant difference between the types of fracture and the demographics of the patients. There were no serious complications and no secondary procedures were required to achieve union. Health-related quality of life measures were available for 60 patients (80%) at a minimum of six months after removal of the frame. These indicated a good return to function (median Paediatric quality of life score, 88.0; interquartile range 70.3 to 100). Conclusion: The Ilizarov method is a safe, effective and reliable method for the treatment of complex paediatric tibial fractures. Cite this article: Bone Joint J 2018;100-B:396–403.